A 30-Year Prospective Follow-Up Study Reveals Risk Factors for Early Death in Cartilage-Hair Hypoplasia - Vakkilainen, Svetlana; Taskinen, Mervi; Klemetti, Paula; Pukkala, Eero; Mäkitie, Outi (Frontiers in Immunology, 2019)
Cartilage-hair hypoplasia (CHH) is a skeletal dysplasia with combined immunodeficiency, variable clinical course and increased risk of malignancy. Management of CHH is complicated by a paucity of long-term follow-up data, as well as knowledge on prognostic factors. We assessed clinical course and risk factors for mortality in a prospective cohort study of 80 patients with CHH recruited in 1985–1991 and followed up until 2016. For all patients we collected additional health information from health records and from the national Medical Databases and Cause-of-death Registry. The primary outcome was immunodeficiency-related death, including death from infections, lung disease and malignancy. Standardized mortality ratios (SMRs) were calculated using national mortality rates as reference. Half of the patients (57%, n = 46) manifested no symptoms of immunodeficiency during follow-up while 19% (n = 15) and 24% (n = 19) demonstrated symptoms of humoral or combined immunodeficiency, including six cases of adult-onset immunodeficiency. In a significant proportion of patients (17/79, 22%), clinical features of immunodeficiency progressed over time. Of the 15 patients with non-skin cancer, eight had no preceding clinical symptoms of immunodeficiency. Altogether 20 patients had deceased (SMR = 7.0, 95%CI = 4.3–11); most commonly from malignancy (n = 7, SMR = 10, 95%CI = 4.1–21) and lung disease (n = 4, SMR = 46, 95%CI = 9.5–130). Mortality associated with birth length below −4 standard deviation (compared to normal, SMR/SMR ratio = 5.4, 95%CI = 1.5–20), symptoms of combined immunodeficiency (compared to asymptomatic, SMR/SMR ratio = 3.9, 95%CI = 1.3–11), Hirschsprung disease (odds ratio (OR) 7.2, 95%CI = 1.04–55), pneumonia in the first year of life or recurrently in adulthood (OR = 7.6/19, 95%CI = 1.3–43/2.6–140) and autoimmunity in adulthood (OR = 39, 95%CI = 3.5–430). In conclusion, patients with CHH may develop adult-onset immunodeficiency or malignancy without preceding clinical symptoms of immune defect, warranting careful follow-up. Variable disease course and risk factors for mortality should be acknowledged.